Changing Organizational Designs and Performance Frontiers - Van de Ven, Andrew H.; Leung, Ricky; Bechara, John P.; Sun, Kangyong (Organization Science, 2012)
This paper develops and tests a multilevel organizational contingency theory for designing headquarters–subsidiary relations. We use frontier analysis to overcome problems that have hampered advancements in organizational contingency theory in general and headquarters–subsidiary relationships in particular. Based on a longitudinal study of a large medical group practice of 32 local community clinics, we compute the relative distance of clinics from a best-performance frontier, determine what proportions of changes in clinic performance are due to factors that are endogenous or exogenous to the clinics, and examine the organizational factors that may explain these performance changes. We find that uniform headquarters policies have differing effects on the performance of subsidiary units, benefiting some and hindering others through no fault of their own. We also find significant performance volatility with different types of unit designs, suggesting the need to examine the risks of changing organization designs.